Al Kalimãtu al Musta’ãratu al ‘Arabiyyatu fī “Jambi Malay Dictionary (Dialect of Jambi Seberang) Indonesia” (Dirãsatun Taḥlīliyyatun fī ‘Ilmi al Aṣwãti) - Rahmadini, Ayu; Prihartini, Yogia (Al-Uslub: Journal of Arabic Linguistic and Literature, 2023)
This article aims to describe the process of phonological changes in Arabic loanwords in the "Jambi Malay Dictionary Jambi Dialect Seberang-Indonesia". The theory used in this article is the theory of sound change proposed by Crowly (1987). The source of this research data was obtained from "Jambi Malay Dictionary (Dialect of Jambi Seberang) Indonesia" and " Dictionary of Indonesian-Arabic Al-Munawwir". The data collection technique used is to use the listen method with record and read techniques. The data analysis method used is the translational padan method. The results showed that it can be concluded that thephonological changes of Arabic loanwords in the "Jambi Malay Dictionary (Dialect of Jambi Seberang) Indonesia" are divided into two aspects based on Crowly's theory. First, Lenisi is a sound attenuation consisting of double consonant reduction, afferesis, and apocope. Pattenuation of letter sounds occurs in the /q/ sound to the /k/ sound when it is located at the beginning of a word and the /q/ sound to become a /ʔ/ sound when it is located at the end of a word; the /kh/ sound becomes the /h/ sound; attenuation from the high vowel /û/ to the medium vowel /ʊ/; Attenuation of sounds also occurs in /ṭ/ to /t/ sounds; weakening of the sound of the sound /r/ into the sound /R/ which is similar to the sound /gh/ in the speech of Jambi Malay dialect Seberang. Second, there is a strengthening of the letter sound in Arabic absorption words in the Seberang dialect of Jambi Malay. Letter sound reinforcement occurs in the /t/ sound as a stronger sound that is a change from /h/; the change in the /p/ sound is seen as a stronger sound than the /f/ sound in the Jambi Malay (dialect of Seberang Jambi).